Assistance of Amanah Farmer Women's Group in Increasing Product Value Added Through Packaging and Label Design in Limapuluh Kota Regency - Iis Ismawati; Raeza Firsta Wisra; Imelfina Musthafa; Riva Hendriani (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Kelompok Wanita Tani (KWT) Amanah is one of the SME groups that processes cassava into tradisional snacks of West Sumatra. Most products are sold wholesale, do not have labels and packaging, so the selling price is lower than the market price. The lack of knowledge of group members about the importance of product packaging and labels still an obstacle. The purpose of this community dedication is to provide awareness to the KWT Amanah community about the importance of labels and packaging in increasing product added value. In addition, the implementation team provided assistance in arranging P-IRT. The method used is trainning, discussion, observation and demonstration. This counseling activity provides insight and knowledge that can motivate KWT Amanah to make decisions in choosing the type of packaging used. This community dedication program are improves value added products through label designs, increase members knowledge and create the products selling value for partner.